Ultrasound assessment of diaphragm thickness in COPD - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
Objective: Thickness of the diaphragm was evaluated by B-mode ultrasonography (US) in chronic obstructive pulmonary disease (COPD) to determine the relationship between diaphragm thickness measurement, pulmonary function tests, and symptom scores. Patients and Methods: Fifty-three clinically stable patients with COPD were enrolled in this study for diaphragmatic thickness evaluation with B-mode US. The severity of COPD was determined by spirometric measurements in terms of %FEV1. Patients were also analyzed according to GOLD criteria. Correlation between diaphragm thickness and symptom scores like Medical Research Council (mMRC), COPD Assessment Test (CAT), composite scores and body mass index (BMI) were sought. Results: There was a moderate correlation between diaphragmatic muscle thickness and %FEV1 in mild COPD patients (r=0.62, p=0.017<0.05). No significant difference in diaphragmatic thicknesses of GOLD subgroups was found. There were no correlations between diaphragmatic muscle thickness, symptom scores, BMI, age, and gender. Conclusion: No correlation was found between diaphragmatic thickness in COPD patients and pulmonary function tests except for %FEV1 in mild COPD patients. There were no correlations between diaphragmatic muscle thickness and symptom scores. Further US studies should take place for functional evaluation of the diaphragm in COPD subgroups.
Keywords: Diaphragm; Ultrasonography; Chronic obstructive pulmonary disease; Thickness